KAPABILITAS PERSONAL DAN PELATIHAN E-KINERJA TERHADAP KEPUASAN PENGGUNA SISTEM E-KINERJA PADA SATUAN KERJA PERANGKAT DAERAH DINAS PEMERINTAH DI KOTA BANDA ACEH - Teuku Try Syahputra Negara; Rudy Fachruddin (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
This research is aimed to verify the influences of personal capability, and e-kinerja training towards the e-kinerja system user satisfaction on SKPD (Satuan Kerja Perangkat Daerah) Dinas Pemerintah in Banda Aceh, those are Dinas Pengelolaan Keuangan dan Aset Daerah; Dinas Syariat Islam; Dinas Pendidikan Pemuda dan Olahraga; Dinas Kesehatan; Dinas Perhubungan, Komunikasi, dan Informatika; Dinas Pekerjaan Umum; Dinas Sosial dan Tenaga Kerja; Dinas Kependudukan dan Pencatatan Sipil; Dinas Perindustrian dan Perdagangan, Koperasi UKM; Dinas Kelautan, Perikanan, dan Pertanian; Dinas Kebersihan dan Keindahan Kota; and Dinas Kebudayaan dan Pariwisata. The populationin this researchare the civil servants who works and uses the e-kinerja system at theSKPD Dinas Pemerintah in Banda Aceh. There are 91 people randomly selected.The collecting of data and information needed in this research was done by field research. The data used is a primary data collected directly from the subjects of research by using questionnaire form. The testing of the influences of independent variables towards dependent variable was done by using multiple regressions model.The result of this research shows that partially, personal capability do not have significant effect towards the e-kinerja system user satisfaction, while e-kinerja training has significant effect towards the e-kinerja system user satisfaction. Meanwhile, simultaneously, personal capability and e-kinerja training have a significant effect towards the e-kinerja system user satisfaction on SKPD Dinas Pemerintah in Banda Aceh.Keywords: user satisfaction, personal capability, training, and e-kinerja